Yield stability of water yam (Dioscorea alata L) landraces compared to improved varieties across multiple environments and their culinary qualities in the Republic of Benin - Dansi, M.; Loko, Y.; Codjia, E.; Fakorede, J.; Agre, A.P.; Amegan, A.; Adomou, A.; Dassou, G.H.; Dansi, A. (2025)
Background In the Republic of Benin, the fresh yam market has two key periods: a time of high availability from August to February, followed by a scarcity from March to July. Fortunately, when Dioscorea rotundata fresh tubers become scarce and expensive, Dioscorea alata (commonly known as Agaabidjan/ Florido) pervades the market and provides a substitute, ensuring income for all value chain actors. Despite its importance, the gene pool of water yam is low and vulnerable in the growing areas.